Optimizing Digital Application Development Through Design Thinking: A Case Study of Finpay Partners at PT Finnet Indonesia - Nurhaya Thahir; Astri Ghina (Journal of Applied Business and Technology, 2025)
Mitra Finpay, a digital financial service application developed by PT. Finnet Indonesia, aims to support business management, particularly for Micro, Small, and Medium Enterprises (MSMEs). Launched in late 2020 and available on both the Play Store and App Store, the application has garnered a significant user base. However, active users remain minimal, and the app's rating lags behind competitors. Initial user interviews revealed discomfort and usability issues as key concerns. This study aims to identify and address user needs for Mitra Finpay by applying the design thinking methodology. Using a descriptive qualitative approach, data were gathered from external stakeholders (users) and internal stakeholders (developers and experts). The design thinking process comprised five stages: empathize, define, ideate, prototype, and test. During the empathize stage, interviews and observations were conducted to create user journey maps, empathy maps, and identify pain points. The define stage prioritized these problems and generated frameworks such as jobs-to-be-done, points of view, and "how might we" statements. Solutions were brainstormed during the ideate stage, focusing on user-centric features. The research resulted in a prototype featuring five new functionalities: onboarding, non-QRIS registration, AI-powered registration data verification, a non-QRIS dashboard, and QRIS registration. Usability testing scored the prototype at 86, deemed acceptable, with positive feedback from participants. Suggestions on onboarding, data completion forms, and dashboard design were promptly addressed, indicating a practical pathway for improving user experience and enhancing application adoption.